Childhood obesity and parental perceptions in a rural Australian population: A pilot study. (6th October 2013) - Spargo, Matthew; Mellis, Craig
<x xml:space="preserve">Abstract</x> Aim While it has been widely recognised in Australian and overseas studies that parents tend to underestimate the weight of their overweight or obese child, there is an opportunity for further research within rural populations. The aim of this study was to assess the agreement between a parent's perception of their child's weight category and the child's measured body mass index (BMI). Methods Cross‐sectional pilot study in Dubbo, a large regional centre in western New South Wales in Australia. Ninety‐three subjects between the ages of 2 and 17 were recruited from the paediatric inpatient unit of the region's base hospital. Trained nursing staff undertook the anthropometric measurements, while a parent or caregiver was asked to complete a questionnaire assessing their perception of their child's weight category. Results Thirty‐two per cent (30/93) of all parents underestimated the weight category of their child, while only 2% (2/93) of parents overestimated their child's weight category. Overall, 66% (61/93) of parents correctly identified their child's measured weight category. Twenty‐nine per cent (27/93) of the sample population was overweight or obese, and in these children, 89% (24/27) of parents underestimated the weight category of their child. Conclusion There is a major discrepancy between the child's measured BMI and their parent's perception of their child's weight category. This finding is consistent with similar past research and has important implications for the management of obesity in children. Further qualitative research may be helpful in ascertaining the reasons for this discrepancy.